PET slikanje in kvantitativna analiza slik pri demencah - Simonič, Jasmina (Matrika, 2020)
Dementia is a broad category of brain diseases characterized by decreased cognitive abilities, such as memory, thinking or orientation. Diagnosis of dementia is made by using cognitive tests and brain imaging by positron emission tomography (PET). For PET, a biomarker is used in imaging, which is a simply measurable physiological parameter relevant to the clinical description of the disease state. The most suitable biomarker for different diseases where metabolic brain activity is altered is radiotracer 18F - fludeoxyglucose. Analysis of PET images is done by two different methods - Statistical parametric mapping or SPM, and Scaled subprofile model/Principal component analysis or SSM/PCA.
Keywords: demenca; dementia; medical imaging; medical physics; medicinska fizika; medicinsko slikanje; positron emission tomography; pozitronska emisijska tomografija